Defense Mechanism In Anton Chekhov's The Seagull: A Psychoanalytic Approach - TRIYONO, TRIYONO (2012)
The study is about how defense mechanism is reflected in Anton Chekhov's The Seagull. The aim of this study is to the major's character personality based on the structural elements and the psychoanalytic perspective of Sigmund Freud. In analyzing The Seagull, the researcher uses the psychoanalytic approach and qualitative method. This research has several benefits to give additional information which can be used by the other literature researchers who are interested in analyzing this play. This study is using two data sources, namely primary and secondary data source. The primary data source is the manuscript of the play itself, while the secondary data are taken from some information needed. The method of data collection is qualitative research. For the last, the writer makes an analysis of Constantine's character using defense mechanism. The analysis is started by analyzing his id, Ego, Superego, anxiety and then his defense mechanism. The analysis of the previous chapter brings this study into following conclusions. First, based on the structural analysis, it appears that in this play Anton Chekhov wants to deliver message that life does not always run as we expected. Second, based on the psychoanalytic analysis it shows the conflicts between Id, Ego, and Superego in the major character cause anxiety.